Restoration of coastal ecosystems: Enhancing community involvement in mangrove adoption in Mampie, West Sulawesi - Putera, Alexander Kurniawan Sariyanto; Yunus, Muh. Rizal Kurniawan; Isdaryanti, Isdaryanti; Tahar, Musrifah; Aslam, Muhammad (Universitas Muhammadiyah Magelang, 2025)
Mampie Hamlet, West Sulawesi, is experiencing coastal abrasion, increasingly frequent tidal flooding, and water pollution that threaten the environment and community economy. Previous efforts, such as the installation of breakwaters, have not been effective in addressing these issues. This community service aims to increase community awareness and involvement in coastal conservation through a mangrove adoption system. The methods include focus group discussions (FGDs) with stakeholders, participatory visual-based training, and mangrove planting and monitoring at two locations. Four hundred forty-five mangrove seedlings were planted using an adoption system involving the community, schools, and universities. Monitoring over three months showed that 87% of the mangroves survived at the first location, while the second location experienced higher losses due to waste and environmental disturbances. From these results, the mangrove adoption system effectively increases community participation and planting success, although further support is needed in waste management and environmental awareness to maintain the achieved results.